The intellectual and artistic dimensions in the circular shape and its relationship with the modern painterly compositions (Damascus University Journal for engineering sciences, 2021)
This research highlights the importance of the circular shape and its presence in the building of the modern painterly compositions, which is one of the most important geometric shape for what it possesses of aesthetic, plastic, symbolic and philosophic values. The research aims at maintaining the concept of the circle and its distinctive characteristics, the impact of the other geometric shapes on it and the reciprocal effect. Then, it stands at its relationship with the elements of composition and its link with the circle through the process of the artistic construction. Finally, the research addresses the highlighting of the intellectual and artistic values of the circles during its presence in some ancient arts generally and in the trends and the plastic arts works in particular. In the conclusion, the research stands at the main findings
Keywords: The dimensions; The intellectual; The artistic; the circular shape; compositions; the modern painterly